2017
DOI: 10.1039/c7nj00866j
|View full text |Cite
|
Sign up to set email alerts
|

Photorelease of nitric oxide (NO) on ruthenium nitrosyl complexes with phenyl substituted terpyridines

Abstract: Transandcisisomers of ruthenium nitrosyl complexes release NO upon irradiation by visible light and give a unique photoproduct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 53 publications
6
49
1
Order By: Relevance
“…Another way is to bubble NO gas on the starting complex [R-tpyRuCl 3 ]: only the cis and trans isomers are formed with the trans one as major compound. 12 Thus, by bubbling NO on the starting compound [NEt 2 -Ph-tpyRuCl 3 ], we obtained two series of complexes: i) the cis/trans-(Cl,Cl)-[Ru(NEt 2 -Phtpy)Cl 2 (NO)] + (as expected) and ii) the cis/trans-(Cl,Cl)-complexes with a modified Phtpy on the amine function (see Scheme 1).…”
Section: Synthesismentioning
confidence: 54%
See 1 more Smart Citation
“…Another way is to bubble NO gas on the starting complex [R-tpyRuCl 3 ]: only the cis and trans isomers are formed with the trans one as major compound. 12 Thus, by bubbling NO on the starting compound [NEt 2 -Ph-tpyRuCl 3 ], we obtained two series of complexes: i) the cis/trans-(Cl,Cl)-[Ru(NEt 2 -Phtpy)Cl 2 (NO)] + (as expected) and ii) the cis/trans-(Cl,Cl)-complexes with a modified Phtpy on the amine function (see Scheme 1).…”
Section: Synthesismentioning
confidence: 54%
“…We planned to find out whether these substituents had any influence on the Ru(NO) / Ru(ON) photoisomerization and on the NO photorelease. 11,12 In addition, DFT calculations were carried out to elucidate the mechanism of release. 13 Similarly, this particular study focuses on the two cis/trans-(Cl,Cl)-[Ru(R-Phtpy)Cl 2 (NO)] + isomers with NEt 2 as R on the 4'-position of the Phtpy (Scheme1).…”
mentioning
confidence: 99%
“…Importantly, disorder appears at the NO 2 -ligand, which was successfully resolved by introducing both a nitro group and a chlorine atom in a ratio 90:10 after refinement with a Ru-Cl distance of 2.32(2) Å. This distance falls in the 2.317(3)-2.394(1) Å range of Ru-Cl bond lengths observed for our previously described [Ru II (R-terpyridine)-(Cl) 2 (NO)](PF 6 ) complexes [21] and therefore appears to be chemically satisfactory. The unexpected presence of chlorine in the crystal structure is likely related to the fact that H is synthesized from complex G, which contains the RuCl moiety instead of Ru(NO 2 ).…”
Section: Structural Studiesmentioning
confidence: 94%
“…On the other hand, we have recently observed that for a series of [Ru II (R-terpy)(Cl) 2 (NO)] + complexes, there is no clear correlation between the donating/withdrawing character of R and the φ NO values. [21] Furthermore, a recent theoretical investigation has suggested that the NO· release could require more than one photon with the contribution of an intermediate triplet state. [38] Altogether, these features tend to suggest that enhancing the donating capabilities of the ligands may not be the only fruitful strategy in this approach towards efficient NO· donors, which could also encompass molecules of greater complexity [e.g., polymetallic Ru(NO) complexes] than those envisioned in the initial stage of these investigations.…”
Section: Additional Considerations Of φ No and σ Tpamentioning
confidence: 99%
“…Ruthenium nitrosyl complexes have attracted considerable interest over the last decades because of their multifunctional photoresponsive capability. Indeed, these complexes can display photochromism in the solid state [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] and be efficient agents for NO photorelease in solution [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Despite the numerous studies exploiting these two distinct photoreactivities (i.e., N→O linkage photoisomerization and photoinduced NO delivery), the underlying mechanisms are notoriously complex to unravel based on the available experimental observations [12,30].…”
Section: Introductionmentioning
confidence: 99%